2022
DOI: 10.29303/ipr.v5i3.162
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOCATALYST ACTIVITY OF MgO FROM BANGKALAN DOLOMITE

Abstract: In the industrial sector, water pollution due to dye waste needs special attention because it can harm humans and the environment. A waste-absorbing material with good photocatalytic properties is required to overcome this problem. The photocatalytic properties are owned by metal oxide materials, one of which is Magnesium Oxide (MgO) material. This study aims to analyze the activity level of MgO photocatalytic from Bangkalan dolomite. MgO synthesis was carried out by the leaching method, where UV-Vis character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Referring to research from Rahmawati and Rohmawati [11], they synthesized MgO using the leaching method, first by sifting dolomite powder using a 200-mesh sieve. Furthermore, 50 g of dolomite was dissolved in 210 mL of 5 M HCl and then stirred using a stirrer at 300 rpm at 75 °C until a solution formed a slurry.…”
Section: Synthesis Of Mgo From Dolomite Bangkalanmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to research from Rahmawati and Rohmawati [11], they synthesized MgO using the leaching method, first by sifting dolomite powder using a 200-mesh sieve. Furthermore, 50 g of dolomite was dissolved in 210 mL of 5 M HCl and then stirred using a stirrer at 300 rpm at 75 °C until a solution formed a slurry.…”
Section: Synthesis Of Mgo From Dolomite Bangkalanmentioning
confidence: 99%
“…The photocatalytic activity of MgO is very effective, considering that the removal of dyes in water by coagulation, flocculation, and adsorption techniques only moves the dyes from the liquid phase into the solid phase and does not decompose the compounds in the dyes so that the color particles can agglomerate and cause new pollution. Research conducted by Rahmawati and Rohmawati [11] showed the photocatalyst process using MgO on methylene blue dye, which was carried out under sunlight, UV light, and dark room with a time of 180, 240, and 300 min showing a degradation rate of 82, 42, and 34 %, respectively. Yadav et al [12] pointed out the same regarding the effectiveness of MgO in photocatalytic activity to degrade methylene blue dye under sunlight and UV light, with degradation percentages of 97 and 92 %, respectively.…”
Section: Introductionmentioning
confidence: 99%